HUBUNGAN ANTARA PARITAS DAN UMUR IBU DENGAN KEJADIAN RETENSIO PLASENTA - Agustin, Leonita Dwi (JURNAL KESEHATAN TERAPAN, 2021)
Labor is the process of expulsion of the fetus, placenta, and amniotic membranes from the uterus through the birth canal. This process begins with cervical dilatation and dilatation due to uterine contractions with regular frequency, duration and force. At first the strength is small, then continues to increase until the surface of the cervix is ​​complete so that it is ready for the fetus to be expelled from the mother's womb. Objective: To determine the relationship between parity and maternal age with the incidence of retained placenta. The design of this study is an analytical study with a cross sectional method approach, this study uses secondary data with a population of 2042 mothers who gave birth and the number of samples taken from simple random sampling, namely simple random sampling with a sample of 334 people. Based on bivariate analysis with Chi-Square test showed that there was a relationship between parity value 0.036 < 0.05, there was a relationship between age value = 0.047 < 0.05 with the incidence of retained placenta. Conclusion Stay more active in improving health promotion to improve the quality of health services in hospitals, among others, by improving planning in providing health services to patients, especially in cases of retained placenta . Keywords: Parity, Age, and Placental Retention